Escape - Tanenbaum, Robert (New York : Pocket Star Books, 2008)
Manhattan D.A. Roger Butch Karp and his crime-fighting crew must race against the clock to stop a malicious terrorist plot that could change the course of history.
Keywords: Karp, Butch (Fictitious character) -- Fiction; Ciampi, Marlene (Fictitious character) -- Fiction; Terrorists -- Fiction; New York (N.Y.) -- Fiction